COVID-19 prevalence and mortality in patients with cancer and the effect of primary tumour subtype and patient demographics: a prospective cohort study. - Lee, LYW; Cazier, J-B; Starkey, T; Briggs, SEW; Arnold, R; Bisht, V; Booth, S; Campton, NA; Cheng, VWT; Collins, G; Curley, HM; Earwaker, P; et al. (Elsevier, 2020)
Background Patients with cancer are purported to have poor COVID-19 outcomes. However, cancer is a heterogeneous group of diseases, encompassing a spectrum of tumour subtypes. The aim of this study was to investigate COVID-19 risk according to tumour subtype and patient demographics in patients with cancer in the UK.